2021
DOI: 10.3389/fchem.2021.634663
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Modeling for Multi-Target Drug Discovery: Designing Simultaneous Inhibitors of Proteins in Diverse Pathogenic Parasites

Abstract: Parasitic diseases remain as unresolved health issues worldwide. While for some parasites the treatments involve drug combinations with serious side effects, for others, chemical therapies are inefficient due to the emergence of drug resistance. This urges the search for novel antiparasitic agents able to act through multiple mechanisms of action. Here, we report the first multi-target model based on quantitative structure-activity relationships and a multilayer perceptron neural network (mt-QSAR-MLP) to virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 82 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Therefore, we calculated a series of topological indices that fused chemical and biological information. To do so, we employed an adaptation of the Box-Jenkins approach, which is the key of the PTML modeling philosophy and for which great successful applications in different research areas have been reported in the scientific literature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 55 , 56 , 57 ]. In the first step of this approach, we used the following mathematical formula: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we calculated a series of topological indices that fused chemical and biological information. To do so, we employed an adaptation of the Box-Jenkins approach, which is the key of the PTML modeling philosophy and for which great successful applications in different research areas have been reported in the scientific literature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 55 , 56 , 57 ]. In the first step of this approach, we used the following mathematical formula: …”
Section: Methodsmentioning
confidence: 99%
“…Particularly, as depicted in Table 1 , the purpose here was to build an mtc-QSAR-MLP model to predict the inhibitory activity of a molecule under eight different experimental conditions. As mentioned in the previous section, such a capability of simultaneously predicting complex biological endpoints under dissimilar experimental conditions is an intrinsic characteristic of any PTML model [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new protocol called mt-QSAR-MLP uses QSAR for the application of multi-target drug discovery against parasitic diseases and aims to predict inhibitors that target proteins of various parasites, simultaneously. This protocol afforded derivatives, e.g., compound 37 that successfully inhibit DHFR-TS, as well as enzymes of other parasites [ 96 ].…”
Section: Drug Targets and Inhibitorsmentioning
confidence: 99%
“…ebi.ac.uk/chembl/, accessed on 7 June 2021) comprises a total of 1892 compounds with activity estimated against MNKs under different experimental conditions (c j ). The latter are better expressed as an ontology [10][11][12][13] of the form c j → (b t , m e , a t ), that is, by defining them according to the following elements: b t -the 'biological target', accounting for the specific MNK enzyme isoform against which the compounds have been tested, m e -the kind of 'measures of biological effects' considered, namely, half-maximal inhibitory concentration (IC 50 ), inhibition (K i ) or dissociation (K d ) constants, and a t -the 'assay type', focusing on either the binding affinity (B) or functional (F) responses. As such, each data-point of the input dataset pertains to one specific combination of the elements b t , m e , and a t or experimental condition c j , and then classified into two categories: positive (IAc j = +1; for high inhibitory potential) or negative (IAc j = −1; for low inhibitory potential).…”
Section: Dataset and Calculation Of Molecular Descriptorsmentioning
confidence: 99%